Natural Vibration of an Initial Stressed Rectangular Composite Thick Plate with Two Neighboring Oval Cylindrical Holes - Akbarov, S. D.; Yahnioglu, N.; Yesil, U. B. (TECHNICAL UNIVERSITY LIBEREC, 2011)
In this work the natural vibration of an initially statically stressed composite rectangular plate containing two neighboring oval cylindrical holes is studied. The considered plate is simply supported all its edges and two neighboring oval cylindrical holes lying width-wise in the plate are placed inside. It is supposed that initial stresses are caused by uniformly distributed normal forces applied on the opposite two end planes of the plate and the investigations are carried out within the framework of the three-dimensional linearized theory of elastic waves in initially stressed bodies. Numerical results are obtained by employing FEM.
Keywords: Initial stress; natural vibration; oval cylindrical hole; fundamental frequency; rectangular plate; 3D finite elements method; Engineering